2007
DOI: 10.1159/000101057
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 Regulates Transforming Growth Factor-β Signaling in Cultured Human Bronchial Epithelial Cells

Abstract: Background: The basic pathological features of bronchial asthma can be explained on the basis of chronic airway inflammation, involving inflammatory cells such as T cells (particularly type 2 helper T, Th2, cells) and mast cells, and airway remodeling. Many aspects of airway remodeling remain unclear at the molecular level. Recent attention has focused on the role of transforming growth factor (TGF)-β, a fibrogenic cytokine, in airway remodeling. Currently available evidence suggests that airway remodeling is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…This view, however, is rapidly changing because of the discovery that airway smooth muscles can undergo hyperplasia and/or hypertrophy, which can lead to structural changes in the airway obstruction and increased nonspecific airway hyperreactivity in chronic severe asthma [25, 26]. In addition, more recent studies have concentrated on the phenotypic transition of ASMCs from the contractile type to a more synthetic type in chronic asthmatics that enable the cells to gain secretory ability and become a rich source of many cytokines, chemokines and inflammatory mediators, which may modulate airway inflammation and processes of airway remodeling in asthma [27,28,29,30,31]. …”
Section: Discussionmentioning
confidence: 99%
“…This view, however, is rapidly changing because of the discovery that airway smooth muscles can undergo hyperplasia and/or hypertrophy, which can lead to structural changes in the airway obstruction and increased nonspecific airway hyperreactivity in chronic severe asthma [25, 26]. In addition, more recent studies have concentrated on the phenotypic transition of ASMCs from the contractile type to a more synthetic type in chronic asthmatics that enable the cells to gain secretory ability and become a rich source of many cytokines, chemokines and inflammatory mediators, which may modulate airway inflammation and processes of airway remodeling in asthma [27,28,29,30,31]. …”
Section: Discussionmentioning
confidence: 99%
“…AM directly contribute to surfactant metabolism and are thought to be crucially involved in the generation of acute as well as chronic allergic reactions of the respiratory tract. In this context, the biology of AM has been extensively studied and both protective as well as detrimental functions of AM could be elucidated in different models of asthma and allergic airway diseases [7,8,9,10,11,12,13,14,15]. Previous studies have suggested that AM may also play a role in the development of secondary pulmonary disorders like acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] The underlying mechanism of antifibrotic effects of IL-10 remains unclear, but it has been suggested that IL-10 can suppress extracellular matrix synthesis and inhibit key inflammatory pathways such as NF-kB. [13][14][15] In the context of kidney, IL-10 has been reported to effectively suppress the progression of acute and chronic renal damage in vivo. [16][17][18][19][20][21][22] However, the role of IL-10 in renal tubulointerstitial fibrosis has not been studied.…”
mentioning
confidence: 99%